Persetujuan Majelis Kehormatan Notaris Atas Pemanggilan Notaris Dalam Pemeriksaan Tindak Pidana - Moeh Angga Nugraha (Officium Notarium, 2021)
Article 66 paragraph 1 of Law Number 2 of 2014 on Notary Position is intended to provide protection for notaries in the running of their profession. On the other hand, the article has disabled legal enforcers from immediately summoning or asking for an authentic deed made by a notary without the approval of the Notary Honorary Council (MKN). In response, material review of the article was conducted and it was ruled in the decision of the Constitutional Court Number 16/PUU-XVIII/2020. Derived from this description, the first problem arises, whether MKN can hinder the criminal examination process? Second, has the Constitutional Court's decision been satisfied as a decision based on justice, expediency and legal certainty? This is a normative legal research and with study through the statutory, conceptual, and case approaches. The results of this study conclude that first, the authority of the MKN in Article 66 of the UUJNP does not considerably hinder the law enforcement process and is part of the protection of the notary profession. Second, the Constitutional Court's decision has provided benefits for the general public who use notary services while maintaining the authority of the MKN. Then in terms of legal certainty, Article 66 becomes the basis for the limits of the MKN's authority to provide approval for investigators, public prosecutors and judges in summoning a notary or examining other files for judicial purposesKey Word: Notary Honorary Council; Public Notary; Constitutional Court DecisionAbstrakPutusan Pasal 66 ayat 1 Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris dimaksudkan untuk melindungi notaris dalam pelaksanaan profesinya. di sisi lain, pasal tersebut membuat pengak hukum tidak serta merta melakukan pemanggilan atau meminta akta otentik yang dibuat oleh notaris tanpa persetujuan Majelis Kehormatan Notaris (MKN). Oleh karenanya terdapat pihak yang melakukan uji materiil terhadap pasal tersebut dan diputus dalam putusan Mahkamah Konstitusi Nomor 16/PUU-XVIII/2020. Dari penjabaran tersebut, muncul permasalah pertama, apakah MKN dapat menghalangi proses pemeriksaan pidana? Kedua, apakah Putusan MK tersebut telah memenuhi sebagai putusan berdasarkan keadilan, kemanfaatan dan kepastian hukum? Penelitian ini merupakan penelitian normatif dan dikaji melalui pendekatan perundang-undangan, konsep, dan kasus. Adapun hasil dari penelitian ini disimpulkan pertama, kewenangan MKN dalam Pasal 66 UUJNP tidak dianggap menghalangi proses penegakan hukum dan menjadi bagian dari perlindungan terhadap profesi notaris. Kedua, Putusan MK tersebut telah memberikan kemanfaatan bagi masyarakat umum pengguna jasa notaris dengan tetap mempertahankan kewenangan MKN. Kemudian, dalam hal kepastian hukum, pasal 66 tersebut menjadi dasar batas kewenangan MKN memberikan persetujuan bagi penyidik, penuntut umum dan hakim dalam melakukan pemanggilan terhadap notaris ataupun memeriksa berkas-berkas lain untuk keperluan peradilan.Kata Kunci: Majelis Kehormatan Notaris; Notaris; Putusan Mahkamah Konstitusi